Student's Perspective on Virtual Laboratory Using Phet as A Media in Conducting Physics Laboratory Activities - Putra, Riki Purnama; Anjani, Rizki Amelia; Agustina, Rena Denya; Suhendi, Herni Yuniarti; Pioren, Melia (Tarbiyah : Jurnal Ilmiah Kependidikan, 2021)
The purpose of writing this paper article is to review students' perceptions in the use of PhET-based virtual labs and also to provide a description in comparison to perceptions of virtual lab use from some of the results of previous studies that are relevant to this study. There are five aspects in the perception that will be surveyed, including; (1) aspects of innovation, (2) aspects of benefits (3) aspects of motivation, (4) aspects of effectiveness, (5) aspects of presenting procedures for laboratory activities. The method used is quantitative and qualitative with a Likert scale questionnaire which must be filled in by 40 people and then interviewing the subjects, after the data is collected, percentage data analysis is carried out. The results of the data analyzed show that the aspects of innovation, effectiveness, benefits and presentation of the procedure get a positive view compared to the motivational aspects which are stated to be negative, so this study also shows that the use of virtual labs based on PhET is innovative and effective, but lacks motivation in its use because of essential activities. laboratory is not felt, in presenting the module is required to increase 4C Skills to support 21st century skills